Parametric study of passive piles subjected to adjacent surcharge load in extensively deep soft soil - Yi, Shixuan; Gu, Meixiang (Frontiers in Materials, 2022)
This paper modeled a single pile subjected to passive loading due to a new embankment in the extensively soft soil using the three-dimensional finite different method (FDM). Four important parameters (i.e., the pile’s bending stiffness, the distance between the long edge of the loading area and the pile (D), the embankment height, and the cushion thickness) were investigated to evaluate their effects on the deformations and stresses of the passive pile. The displacement of the pile shaft, vertical displacement of the foundation soil, excess pore water pressure (EPWP), and the lateral earth pressure were analyzed. The numerical results show that the lateral displacement of the pile was significantly affected by four parameters. The maximum lateral displacement dramatically decreased for the high stiffness pile. The cushion thickness of less than 1 m slightly increased the pile’s lateral displacement. The increase of D value and the decrease of the embankment height significantly reduced the lateral displacement of the pile. The vertical displacement of the loading area was unaffected by the pile stiffness. The distribution shape of the vertical displacement was close to be symmetrical with the increase of the D value. The embankment height and cushion thickness significantly affected the vertical displacement. Due to the low permeability of the foundation soil and short construction time, the EPWP was not fully dissipated under the variation of the pile stiffness and the D value. The decrease of the pile stiffness increased the lateral earth pressure acting at the pile, while the increase of the embankment height and cushion thickness increased the lateral earth pressure.